Evaluation of Anti-Diarrhoeal Activity of Stem Bark Extracts of Ficus religiosa Prepared by Different Methods of Extraction - S, Panchawat (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT Aims: The purpose of the present study was to evaluate antidiarrhoeal effect of various extracts (hydroalcoholic 60% and acetone extracts) of stem bark of Ficus religiosa Linn. against castor-oil-induced diarrhoeal model in rats. Methods: Antidiarrhoeal activity of hydralcoholic 60% extract (prepared by soxhlet extraction method), acetone extract (prepared by ultrasonication assisted extraction method) and acetone extract (prepared by microwave assisted extraction method) of stem bark of Ficus religiosa Linn. were investigated using castor-oil-induced diarrhea model in rats. The number of faeces and total weight of faeces were studied. Results: Standard drug Loperamide (3mg/kg, p.o.) shows significant reduction in fecal output whereas extracts (hydroalcoholic 60% and acetone extracts) at a dose of 200 mg/kg, significantly (p<0.001) reduced the castor-oil-induced frequency and consistency of diarrhoea. The hydroalcoholic (60%) extract prepared by soxhlet extraction method shows best result than other extracts. Conclusion: The hydroalcoholic (60%) extract shows marked reduction in the number of diarrhea stools and total weight of diarrhoeal faeces. The result obtained establishes the traditional claim of plant as anti-diarrhoeal agent. Further studies are needed to understand the mechanism of anti-diarrhoeal action of Ficus religiosa Linn. stem bark.